Mental health in transgender individuals: a systematic review. (19th May 2022) - Pinna, Federica; Paribello, Pasquale; Somaini, Giulia; Corona, Alice; Ventriglio, Antonio; Corrias, Carolina; Frau, Ilaria; Murgia, Roberto; El Kacemi, Sabrina; Galeazzi, Gian Maria; Mirandola, Massimo; Amaddeo, Francesco; et al.
Abstract: Several lines of evidence indicate the prevalence of mental health disorders in Transgender (TG) individuals is higher than that of cisgender individuals or the general population. In this systematic review, we aim to propose a summary of some of the most significant research investigating mental health disorders' prevalence among this population. We performed a double-blind systematic review using the Preferred Reporting Items for Systematic Reviews and Meta-analyses reporting (PRISMA) on PUBMED/MEDLINE and SCOPUS, specifically using peer-reviewed articles examining the mental health status of transgender (TG) individuals. This review did not exclude any research based on publication date. The last search was performed in February 2022. The employed search strategy led to the selection of 165 peer-reviewed articles. The majority of these papers presented a cross-sectional design with self-reported diagnoses and symptoms, signaling a significant prevalence of mental health disorders amongst TG Individuals. Of the reviewed articles, 72 examined the prevalence of mood and anxiety disorders; 8 examined eating disorders; 43 examined the prevalence of suicidal or self-harm ideation or behaviors; 5 papers examined the prevalence of trauma and stress-related disorders; 10 examined the frequency of personality disorders; 44 examined substance use disorders; and 9 papers examined the prevalence of autism spectrum disorder. Finally, 22 studies reported on the prevalence of TG individuals diagnosed with co-morbid mental health disorders or unspecified mental disorders. Our findings coincide with existing research, which indicates TG individuals do experience a higher prevalence of mental health disorders than that of the general population or cisgender individuals. However, further research is needed to address the existing gaps in knowledge.